"Virtual" Eucharists in a Time of COVID-19 Pandemic: Biblical, Theological and Constitutional Perspectives - Douglas, Brian (Journal of Anglican studies, 2020)
This article examines the possible use of "virtual" Eucharists in the Anglican Church of Australia in a time of a global pandemic such as exists in the world in 2020 with the spread of coronavirus or COVID-19. The changing nature of modern communication is considered in the context of the possibility of the use of a ‘virtual’ Eucharist, where a priest in one place with a set of bread and wine, consecrates the bread and wine, while at the same time a person in their own home consumes another set of bread and wine with the assumption that second set of bread and wine is also consecrated. Suggestions for and discussion of the use of a ‘virtual’ Eucharist in two dioceses of the Anglican Church of Australia are discussed with a consideration of published material by episcopal leaders. Biblical, theological and constitutional perspectives are then considered in relation to a ‘virtual’ Eucharist before the recommendation is made that ‘virtual’ Eucharists are not considered as appropriate at any time, including during a global COVID-19 pandemic, in the Anglican Church of Australia. Several alternatives to a ‘virtual’ Eucharist are considered which would allow people to obtain spiritual nourishment by other means.